2001
DOI: 10.1097/00006534-200107000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Immediate and Delayed Free TRAM Flap Breast Reconstruction in Patients Receiving Postmastectomy Radiation Therapy

Abstract: Tumor pathologic features and the extent of nodal involvement dictate whether radiation therapy is given after mastectomy for breast cancer. It is generally well accepted that radiation negatively influences the outcome of implant-based breast reconstruction. However, the long-term effect of radiation therapy on the outcome of breast reconstruction with the free transverse rectus abdominis myocutaneous (TRAM) flap is still unclear. For patients who need postmastectomy radiation therapy, the optimal timing of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
185
5
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(203 citation statements)
references
References 7 publications
4
185
5
9
Order By: Relevance
“…8). 20 It is also a good option for thin patients who are not candidates for a TRAM flap procedure because of inadequate tissue for reconstruction or for closure of the abdominal donor site. Unlike the tissue-expansion method, breast reconstruction with a latissimus dorsi flap plus an implant can create a ptotic-appearing breast.…”
Section: Choosing the Best Methods Of Reconstruction Is Essential To Omentioning
confidence: 99%
See 2 more Smart Citations
“…8). 20 It is also a good option for thin patients who are not candidates for a TRAM flap procedure because of inadequate tissue for reconstruction or for closure of the abdominal donor site. Unlike the tissue-expansion method, breast reconstruction with a latissimus dorsi flap plus an implant can create a ptotic-appearing breast.…”
Section: Choosing the Best Methods Of Reconstruction Is Essential To Omentioning
confidence: 99%
“…A disadvantage with latissimus dorsi flap-based reconstruction is that the latissimus muscle tends to atrophy over time, which makes the underlying breast implant more pro- minent and can reveal even subtle irregularities in the implant caused by capsular contracture. 20 Breast reconstruction using the patient's own tissues results in the most natural-appearing reconstructed breasts…”
Section: Choosing the Best Methods Of Reconstruction Is Essential To Omentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, postmastectomy irradiation may have a negative impact on breast cosmesis when autologous tissue is used in immediate breast reconstruction, and may interfere with the targeted delivery of radiation when immediate reconstruction is performed using either autologous tissue or breast implants. 129,130 Some studies, however, have not found a significant compromise in reconstruction cosmesis after irradiation. 131 The preferred approach to breast reconstruction for these patients was a subject of controversy among the panel.…”
Section: Breast Reconstructionmentioning
confidence: 99%
“…Complications with relevant probabilities were included for each treatment based on a PubMed literature review. 5,[11][12][13][14][15][16][17][18][19] Outcomes were considered mutually exclusive to allow probabilities to add up to one; therefore, each patient could have only one complication. The base case analysis for the study was determined using a weighted average of years remaining to live for a typical woman diagnosed at age of 48 years with stage 2 or 3-breast cancer (American College of Surgeons National Cancer Database).…”
Section: Methodsmentioning
confidence: 99%